(untitled) (International journal of artificial intelligence, 2024)
To the person directed teaching technologies modern pedagogical approach of students personal interests, needs, abilities and development level account to get is based on This of approach main purpose of the student individuality develop, his socio-cultural in the environment own place to find help to give and knowledge get process in mastering independent and creative thinking abilities from forming consists ofTo the person directed technologies of application importance in the following manifestation will be: